1999
DOI: 10.1038/sj.bmt.1702048
|View full text |Cite
|
Sign up to set email alerts
|

The number and generative capacity of human B lymphocyte progenitors, measured in vitro and in vivo, is higher in umbilical cord blood than in adult or pediatric bone marrow

Abstract: The number and generative capacity of human B lymphocyte progenitors, measured in vitro and in vivo, is higher in umbilical cord blood than in adult or pediatric bone marrow Summary:The lack of human B lymphocyte development in beige/nude/XID (bnx) mice is in sharp contrast to the robust development observed in another immune deficient strain, the NOD/SCID mouse. The ability to generate human B lymphocytes in the NOD/SCID, but not bnx mouse has been hypothesized to be caused by differences in the microenviron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 15 publications
4
43
1
1
Order By: Relevance
“…Rapid recovery of B-cell numbers after CBT, already described by others, 2,6,8,9 can be attributed to a higher proportion of B-cell precursors in cord blood. 37 B-cell maturation after CBT remains suboptimal at 1-year post-transplant, as already described with other graft sources. 22 As B-cell maturation needs an interaction with CD4 þ T cells in germinal centers, the slow B-cell maturation after CBT may be explained at least in part by the length of CD4 þ maturation.…”
Section: Discussionmentioning
confidence: 68%
“…Rapid recovery of B-cell numbers after CBT, already described by others, 2,6,8,9 can be attributed to a higher proportion of B-cell precursors in cord blood. 37 B-cell maturation after CBT remains suboptimal at 1-year post-transplant, as already described with other graft sources. 22 As B-cell maturation needs an interaction with CD4 þ T cells in germinal centers, the slow B-cell maturation after CBT may be explained at least in part by the length of CD4 þ maturation.…”
Section: Discussionmentioning
confidence: 68%
“…This difference is likely due to the lower frequency of B cell progenitors present in human bone marrow, as compared to umbilical cord blood. 27 In the current study we demonstrated that the percentage of CD19 + B cells that develop from human cord blood CD34 + CD38 − cells in bnx mice is higher after being maintained ex vivo on AFT024 than on human stroma. CD19 + cell engraftment averaged 2.3 ± 0.4% in mice that had been transplanted with cells from the 2-week AFT024 cultures, and 1.0 ± 0.2% in the group transplanted with cells from 2-week HS cultures (Figure 4).…”
Section: Human B Lymphoid Engraftmentmentioning
confidence: 70%
“…27 In the current studies, we estimated that in the 2000 CD34 + /CD38 − cells isolated from umbilical cord blood and seeded into the in vitro cultures, there should have been an average of 60 human hematopoietic progenitors that had the capacity to generate B lymphoid cells, based on calculations that we have previously reported. 27,38 Even if a proportion of the cells had differentiated to maturity during the duration of the culture, a proportion of the cells had remained primitive enough to sustain B lymphopoiesis in the bnx mice following transplantation (Figure 4). In contrast, we have reported that 2000 CD34 + /CD38 − cells from adult or pediatric bone marrow contain an average of only one cell with B lymphopoietic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Especially after transfer of CD34 + cells from UCB, the main cell lineage recovering in the NOD/SCID mice has been reported to be of B cells. [24][25][26][27][28][29] Similarly, we found that after relatively low doses of UCB CD34 + cells 81-95% of the engrafted cells were of B cell origin. At these doses only very low engraftment was found with BM or mPB CD34 + cells, not allowing reliable evaluation of specific cell lineages by flow cytometry.…”
Section: Discussionmentioning
confidence: 94%